Plasma S100A8 and S100A9 Are Strong Prognostic Factors for Hepatitis B Virus-Related Acute-on-Chronic Liver Failure - Yao Zhang; Xueyun Zhang; Jiajia Han; Yifei Guo; Jingjing He; Feifei Yang; Richeng Mao; Yuxian Huang; Jiming Zhang (Canadian Journal of Gastroenterology and Hepatology)
Objectives. The rapidly evolving organ failure and high short-run mortality of acute-on-chronic liver failure (ACLF) are inseparable from the role of systemic inflammatory response. S100A8 and S100A9 are associated with the excessive cytokine storm and play a decisive part within the process of inflammation. We aimed to clarify the role of them in predicting prognosis of hepatitis B virus-related ACLF (HBV-ACLF). Methods. S100A8 and S100A9 levels were analyzed in plasma of 187 transplant-free HBV-ACLF patients, 28 healthy controls and 40 chronic hepatitis B (CHB) patients. S100A8 and S100A9 mRNAs were checked in liver samples from 32 HBV-ACLF patients with liver transplantation, 19 patients undergoing surgery for hepatic hemangioma and 10 CHB patients with needle biopsy. Results. The plasma levels of the S100A8 and S100A9 were higher in HBV-ACLF patients than in CHB patients (S100A8 : P<0.001 and S100A9 : P<0.001) and healthy controls (S100A8 : P<0.001 and S100A9 : P<0.001), and similar results were obtained for mRNA expression. Moreover, both proteins were related to ACLF grade, different types of organ failure, and infection, and they correlated with other prognostic scoring systems. S100A8 and S100A9 can dependently predict 28/90-day mortality (28-day: S100A8: hazard ratio (HR): 1.027; 95% confidence interval (CI): 1.007–1.048; P=0.026, S100A9 : HR: 1.009; 95% CI: 1.001–1.017; P=0.007, 90-day: S100A8 : HR: 1.023; 95% CI: 1.011–1.035; P=0.004, S100A9 : HR: 1.008; 95% CI: 1.004–1.012; and P<0.001). Among all of the scoring systems, the combined scoring model (S100A8 and S100A9 jointly with the Chronic Liver Failure-Consortium Organ Failure score (CLIF-C OFs)) displayed the highest area under the receiver operating curve (0.923 (95% CI, 0.887–0.961)) in the prediction of 90-day mortality. Conclusions. S100A8 and S100A9 are promising biomarkers for the analysis of risk stratification and prognosis in ACLF patients. In addition, combining them with the CLIF-C OFs may better predict the prognosis of ACLF.